2007
DOI: 10.1562/0031-8655(2003)0780384mfemrt2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Fluorescence Excitation-Emission Matrices Relevant to Tissue Spectroscopy¶

Abstract: In vivo and ex vivo studies of fluorescence from endogenous and exogenous molecules in tissues and cells are common for applications such as detection or characterization of early disease. A systematic determination of the excitation–emission matrices (EEM) of known and putative endogenous fluorophores and a number of exogenous fluorescent photodynamic therapy drugs has been performed in solution. The excitation wavelength range was 250–520 nm, with fluorescence emission spectra collected in the range 260–750 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
1
27
0
1
Order By: Relevance
“…Many research groups have reported the autofluorescence around 500 nm as an emission from endogenous fluorophores, like NADH, FAD, collagen, elastin, and amino acids, and emissions at 635 and 705 nm from enhanced PpIX presence in malignant tissues 4–6, 10–12, 23, 24. In addition to these peaks, we noticed a prominent peak around 685 nm in malignant tissues that appears between the PpIX peaks.…”
Section: Discussionmentioning
confidence: 57%
“…Many research groups have reported the autofluorescence around 500 nm as an emission from endogenous fluorophores, like NADH, FAD, collagen, elastin, and amino acids, and emissions at 635 and 705 nm from enhanced PpIX presence in malignant tissues 4–6, 10–12, 23, 24. In addition to these peaks, we noticed a prominent peak around 685 nm in malignant tissues that appears between the PpIX peaks.…”
Section: Discussionmentioning
confidence: 57%
“…Lipids with emission in the 450–660 nm range take part in the calcification process while vitamin D with maximum emission at 480 nm is thought to be a bone‐regulating factor. Moreover, molecular fluorescence excitation–emission matrix relevant to tissue spectroscopy (33) contributes emission from collagen I (predominant in bone) at the end of the short wavelength range taken into consideration in this work. This is essential because collagen makes up approximately 90% of the organic matrix in bone.…”
Section: Resultsmentioning
confidence: 99%
“…Dozens of papers examined the potential in cardiac applications, endoscopy [2] and gynecology [3], using blue and UV light excitation and looking at emission spectra in the blue-green wavelengths. These signals are largely attributed to collagen, NADH, and FAD [4], although identification of the causative nature of the spectra in these layered tissues was a subject of ongoing studies for a decade beyond their initial identification [5] [6]. The confounding effects of tissue layers, light scatter and blood absorption combine to make the spectra harder to interpret.…”
Section: Biochemical Imaging Agentsmentioning
confidence: 99%